PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD MELALUI MEDIA CHART GAME COMPETETION UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL POKOK BAHASAN KEDATANGAN BANGSA-BANGSA BARAT KE INDONESIA DI KELAS VIII A S - Lilik Mulyani (Cakrawala Pedagogik, 2022)
The purpose of this study was to find out the activities and learning outcomes of class VIII students in the Science and Social Sciences subject through cooperative learning type stad. After conducting the research, there was a significant increase from cycle I to cycle II both in student motivation and student learning outcomes. The results of observations on student learning activities in the first cycle were 12 people or 43% of 28 students with an average post-test result of 69.05 students with a completeness score of 57%. In the second cycle of student learning activities, there were 23 students or 82% with an average post-test score of 82.14 with a completeness score of 86%. This indicates that the implementation of Classroom Action Research (CAR) in Class VIII A students of SMP Negeri 1 Jiput, Pandeglang Regency using the STAD Type Cooperative Learning method through the Media Chart Game Competition on the subject of the Arrival of Western Nations to Indonesia Social Studies subjects are very effective and significant.